The role of major virulence factors and pathogenicity of adherent-invasive Escherichia coli in patients with Crohn’s disease - Khalid A. Abdelhalim; Ataç Uzel; Nalan Gülşen Ünal (Gastroenterology Review)
Inflammatory bowel disease (IBD) is a term that describes Crohn’s disease (CD) and ulcerative colitis (UC), and these two conditions are characterised by chronic inflammation of the gastrointestinal tract. Dysbiosis of intestinal microbiota has been consistently linked to patients with IBD. In the last two decades, the progressive implication of adherent-invasive Escherichia coli (AIEC) pathogenesis in patients with CD has been increasing. Here we discuss recent findings that indicate the role and mechanisms of AIEC in IBD. We also highlight AIEC virulence factor genes and mechanisms that suggest an important role in the severity of inflammation in CD patients. Finally, we emphasise data on the prevalence of AIEC in CD patients.